DECOLONISATION OF THE LAW CURRICULUM IN SOUTH AFRICA THROUGH THE PRISM OF A LIVED EXPERIENCE (The Pretoria Student Law Review, 2021)
The current educational system, with a specific focus on legal education, remains based on Eurocentric knowledge with only limited inclusion of African knowledge. The article examines the historical context and the negative impact of colonial legislation on the law curriculum. The biggest problem identified in the law curriculum is that most modules (delete contents) and programmes are not linked to African cultures, realities and do not seek to address or solve African problems. This article argues for the creation of an Afrocentric law curriculum and the development of sufficiently rigorous local knowledge that relates better to the needs of students and the challenges in South Africa, while at the same time contributing to global knowledge production. This will make schools of law produce lawyers who are skilled to solve the problems confronting African people from different cultures. This article proposes solutions on how to decolonise, Africanise and transform the law curriculum.
Keywords: African problems; Afrocentric law curriculum; decolonise; educational system